Synopsis: Accelerating progress in improving diets and nutrition in Ethiopia - Baye, Kaleab; Hirvonen, Kalle (International Food Policy Research Institute, 2020)
Ethiopia has witnessed significant reductions in child mortality, undernutrition and communicable diseases, but more substantial and faster progress is still needed. The rise in overweight and obesity and in non-communicable diseases, particularly in urban areas, is alarming and requires urgent policy and programmatic attention. Unhealthy diets are the drivers of both forms of malnutrition and are the underlying cause of significant proportion of communicable and non-communicable diseases. Maintaining the relatively high breastfeeding practices and increasing the diversity of diets will be critical. Implementation of effective nutrition messaging that shapes consumer behavior to adopt healthy dietary patterns, while bridging gaps in reach and quality of nutrition messaging is warranted. The health extension program that is the cornerstone of the health sector transformation may need to be redesigned in a way that improves reach, quality, and minimize the risk of burnout of frontline health workers. Interventions focusing on making healthy diets affordable, accessible and available are urgently needed.